Termination of Construction Contract under UAE Law - Salous, Ameed (2021)
The dissertation aims to examine the legal principles and practices applicable to terminate construction contracts in UAE. This dissertation identified the causes of termination and showed the drastic effect of the termination on the contracting parties beginning from paying the cost of the performed works until paying the loss of profit or loss of opportunity. The UAE showed a significant level of protection on the performance of the contract refusing to accept the terminations as a prime remedy for the breach of contract and keeping it the last resort. Such protection was clear in the control of the court over the fate of the contract. However, many exceptions allow the automatic termination out of the court, such as force majeure events or by agreement of the parties. The termination without causes still uncertain to be enforced by the courts; nevertheless, there are provisions of law that can be used as a vehicle to try to enforce it. Such a type of termination is necessary as there are economic advantages in applying it. Many uncertainties and shortfalls are noticed in UAE law, from the degree of the breach that allows termination, the definition of the force majeure to the fate of the contractual damages upon the contract’s termination. All are matters need to be treated better by the legislator.